Optimization of Epoxy-Barium Titanate Nanocomposites for High Performance Embedded Capacitor Components - Jianwen Xu; Kyoung-Sik Moon; Pramanik, P.; Bhattacharya, S.; Wong, C.P. (IEEE transactions on components and packaging technologies, 2007)
One of the most promising avenues to meet the requirements of higher performance, lower cost, and smaller size in electronic systems is the embedded capacitor technology. Polymer-ceramic nanocomposites can combine the low cost, low temperature processability of polymers with the desirable electrical and dielectric properties of ceramic fillers, and have been identified as the major dielectric materials for embedded capacitors. However, the demanding requirements of mechanical properties and reliability of embedded capacitor components restrict the maximum applicable filler loading (<50vol%) of nanocomposites and thereby limit their highest dielectric constants (<50) for real applications. In this paper, we present a study on the optimization of the epoxy-barium titanate nanocomposites in order to obtain high performance, reliable embedded capacitor components. To improve the reliability of polymer-ceramic nanocomposites at a high filler loading, the epoxy matrix was modified with a secondary rubberized epoxy, which formed isolated flexible domains (island) in the continuous primary epoxy phase (sea). The effects of sea-island structure on the thermal mechanical properties, adhesion, and thermal stress reliability of embedded capacitors were systematically evaluated. The optimized, rubberized nanocomposite formulations had a high dielectric constant above 50 and successfully passed the stringent thermal stress reliability test. A high breakdown voltage of 89MV/m and a low leakage current of about 1.9times10 -11 A/cm 2 were measured in the large area thin film capacitors